Effects of human milk on blood and bone marrow cells in a malnourished mice model; comparative study with cow milk - Isabel García (Nutrición Hospitalaria, 2013)
Introduction: It has been demonstrated that the alterations caused by nutrient deficiency can be reverted by adequate nutritional repletion. Objective: To perform comparative studies between human and cow milks in order to evaluate the impact of both milks on the recovery of blood and bone marrow cells affected in malnourished mice. Method: Weaned mice were malnourished after consuming a protein free diet for 21 days. Malnourished mice received cow or human milk (CM or HM) for 7 or 14 consecutive days. During the period of administration of milk, the mice consumed the protein free diet ad libitum. The malnourished control (MNC) group received only protein free diet whereas the wellnourished control (WNC) mice consumed the balanced conventional diet. Results and Discussion: Both milks normalized serum albumin levels and improved thymus weight. Human milk was less effective than cow milk to increase body weight and serum transferrin levels. In contrast, human milk was more effective than cow milk to increase the number of leukocytes (WNC: 6.90 ± 1.60a; MNC: 2.80 ± 0.90b; CM 7d: 3.74 ± 1.10b; HM 7d: 7.16 ± 1.90a; CM 14d: 4.35 ± 1.20b; HM 14d: 6.75 ± 1.20a (109/L); p < 0.05) and lymphocytes (WNC: 5.80 ± 0.36a; MNC: 1.80 ± 0.40b; CM 7d: 2.50 ± 0.30b; HM 7d: 4.20 ± 0.50c; CM 14d: 3.30 ± 0.31d; HM 14d: 4.70 ± 0.28c (109/L); p < 0.05) in peripheral blood. Both milks induced an increment in mitotic pool cells in bone marrow and α-naphthyl butyrate esterase positive cells in peripheral blood. They also normalized phagocytic function in blood neutrophils and oxidative burst in peritoneal cells. Conclusion: Both milks were equally effective to exert favorable effects on the number of the bone marrow cells and the functions of the blood and peritoneal cells involved in immune response. However, only human milk normalized the number of leukocytes and increased the number of neutrophils in peripheral blood.